The molecular basis of brain injury in preterm infants with sepsis - associated encephalopathy - Xiaohui Gong; Bowen Weng; Xiaoyue Zhang; Chongbing Yan; Cheng Cai (BMC, 2022)
Abstract Sepsis-associated encephalopathy (SAE) is characterized by brain dysfunction during sepsis, without central nervous system infection. Here, we explored the molecular basis of brain injury in preterm infants with SAE. From Jan 2016 to Dec 2019, a total of 20 preterm infants were hospitalized in the neonatal intensive care unit (NICU) of our hospital, including 10 preterm infants with SAE (SAE group) and 10 preterm infants without encephalopathy after sepsis (no SAE group). Among the 20 premature infants, there were 12 males and 8 females, with mean gestational age 31.0 ± 2.46 weeks, 7 cases with birth weight ≤ 1500 g and 13 cases with birth weight 1500-2500 g. Blood cultures were negative in 6 cases and positive in 14 cases, including 10 cases of Gram-negative and 4 cases of Gram-positive bacteria, respectively. Expression levels of messenger RNA (mRNA) and MicroRNA (miRNA) were analyzed in peripheral blood samples from both groups during sepsis. There were 1858 upregulated and 2226 downregulated mRNAs [fold-change (FC) > |2|, p < 0.05], and 322 upregulated and 160 downregulated miRNAs (FC > |2|, p < 0.05), respectively, in the SAE group compared with the no SAE group. Expression levels of miRNA-1197 [95% confidence intervals (CI), 0.042 to 0.166] were 6.03-fold higher in the SAE group than the no SAE group, while those of miRNA-485-5p (95% CI, 0.064 to 0.024) were lower (0.31-fold). Both high expression of miRNA-1197 and low expression of miRNA-485-5p may be associated with pathogenic alteration of the oxidative respiratory chain and energy metabolism in preterm infants with SAE.